Pengaruh Variasi Kaolin Sebagai Pengganti Sebagian Semen Terhadap Kuat Tekan Mortar - Harahap, Abeng Andhika Pratama; wahyuni, Ade Sri; Gunawan, Agustin; Afrizal, Yuzuar; Islam, Mukhlis (Universitas Bengkulu, 2025)
This study aims to determine the effect of using kaolin on the compressive strength of mortar compared to normal mortar, as well as to identify the optimum percentage of kaolin that yields the highest compressive strength. The research uses an experimental method with references from journals. The test specimens are made using cube molds with dimensions of 5 cm × 5 cm × 5 cm, totaling 100 specimens. Compressive strength tests will be conducted at the ages of 7, 14, 21, and 28 days.The cement replacement variations using kaolin are 10%, 20%, 30%, 40%, and 50%. The highest compressive strength value occurred at the 10% kaolin variation on day 28, with an average strength of 23.8 MPa. Compared to normal mortar, which has a strength of 23.6 MPa, the increase in compressive strength with 10% kaolin is minimal. Meanwhile, mortar with more than 20% kaolin shows a decrease in compressive strength compared to normal mortar.